Learning for the Empowerment of High School Girl Students - Delzo-Zurita, Manuel (2024)
There is a gender gap between men and women, this is manifested in gender violence and social injustice. An alternative to reduce this gap is female empowerment through learning. This study proposes an IT model for the empowerment of girls in high school education, which is based on Moodle and includes six modules (Administrator, Instructional Team, Mentor, Girl, Learning Tools and Empowerment Test). The proposed model was implemented in a system called EmpowerMe that includes the tools digital library, chatbot, webinar and a game-based learning platform. EmpowerMe was validated through a case study over eight student girls in Huancayo, Perú. The results in the case study show that after two sessions of 1.5 h each, the girls’ empowerment improves by 4.18% with the application, in contrast to the traditional method, which improves by 2%, and the usability and satisfaction evaluation show that the EmpowerMe system is rated with an average of 4.43 out of 5 points, obtaining high marks regarding usability, content management, follow-up and user satisfaction.